Eficácia e segurança do rituximab no tratamento da Síndrome de Sjögren primária (SSp): revisão sistemática e metanálise - Souza, Francine Bertolais do Valle [UNIFESP] (2016)
BACKGROUND: Primary Sjögren's Syndrome (pSS) is a systemic autoimmune disease that involves the exocrine glands and internal organs. pSS leads to destruction and loss of secretory function due to intense lymphoplasmacytic infiltration. Therapeutic options include mainly symptomatic and supportive measures, and traditional immunosuppressant drugs have shown no effectiveness in randomized trials. Rituximab (RTX) is a chimeric antibody anti-CD20 that leads to B cell depletion by diverse mechanisms. There is evidence that this drug may be effective for treating pSS. The objective of this systematic review was to evaluate Rituximabeffectiveness and safety for treating pSS. METHODS AND FINDINGS: We conducted a systematic review of RCTs published until December 2015, with no language restriction. We registered a protocol on PlataformaBrasil (40654814.6.0000.5505) and developed search strategies for the following scientific databases: MEDLINE, EMBASE, CENTRAL and LILACS. We included adults with established pSS diagnosis and considered the use ofRTX as intervention and the use of other drugs or placebo as control. Four studies met our eligibility criteria: three with low risk of bias and one with uncertain risk of bias. The total number of participants was 276 (145 RTX, 131 placebo). We assessed the risk of bias of each included study and evaluated the following as primary outcomes: lacrimal gland function, salivary gland function, fatigue improvement and adverse events. We found no significant differences between the groups in the Schirmer test at week 24 meta-analysis (MD 3.59, 95% CI -2.89 to 10.07). Only one study evaluated the lissamine green test and reported a statistically significant difference between the groups at week 24 (MD -2.00, 95% CI -3.52 to -0.48). There was a significant difference between the groups regarding salivary flow rate (MD 0.09, 95% CI 0.02 to 0.16) and improvement in fatigue VAS at weeks 6 (RR 3.98, 95% CI 1.61 to 9.82) and week 16 (RR 3.08, 95% CI 1.21 to 7.80). CONCLUSIONS: According to moderate quality evidence, the treatment with a single RTX course in patients with SSp presents discrete effect for improving lacrimal gland function. Low-quality evidence indicates the potential of this drug for improving salivary flow. According to low quality evidence, no differences were observed in the evaluation after 24 weeks regarding fatigue reduction (30% VAS), serious adverse events occurrence, quality of life improvement and disease activity. With a very low level of evidence, there was no improvement in oral dryness VAS evaluation.